(Re)designing an Online Course in Archival Science Using the ADDIE Model: Lessons Learned and Future Directions - Alaoui, Siham (Journal of education for library and information science, 2025)
This article reflects a teaching experience in an archival science program offered by a Quebec university. With the aim of redesigning an online course in records management intended for undergraduate students, by incorporating more recent aspects in the course curriculum, a pedagogical approach based on the ADDIE model (analysis, design, development, implementation, and evaluation) was chosen to meet learners’ needs. This contribution outlines the instructional design of the course and emphasizes the various processes executed in each phase. The challenges encountered are highlighted, possible solutions are presented, and future research avenues are suggested.